Optimalisasi Kinerja Karyawan melalui Pendekatan Human Capital Management pada UMKM Digital Printing - Rina Loliyana; Rini Loliyani; Andi Surya; Shinta Merinda Ananda (Universitas Mitra Indonesia, 2026)
Employee performance is one of the key factors determining the success of digital printing micro, small, and medium enterprises (MSMEs) in an increasingly competitive business environment. However, many MSMEs still prioritize investment in technology over human resource development, resulting in suboptimal implementation of Human Capital Management (HCM). This study aims to analyze the implementation of Human Capital Management in optimizing employee performance in digital printing MSMEs in Pati Regency, Indonesia. This research employed a qualitative approach using a case study design. Data were collected through direct observation, in-depth interviews, and documentation involving business owners, operational managers, machine operators, graphic designers, and administrative staff selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings reveal that the implementation of Human Capital Management positively contributes to improving employee performance through competency development, continuous learning, knowledge sharing, and skills enhancement. Nevertheless, several challenges remain, including the absence of structured training programs, limited competency evaluation systems, and reward systems that primarily emphasize production targets rather than employee development. This study concludes that optimizing employee performance in digital printing MSMEs requires an integrated Human Capital Management approach encompassing competency development, performance evaluation, continuous learning, and performance-based reward systems. The findings contribute to the development of Human Capital Management practices in MSMEs and provide practical recommendations for business owners to enhance productivity and achieve sustainable competitive advantage